Peningkatan Hasil Belajar Kognitif: Implementasi Model Pembelajaran NHT Materi Atmosfer Berbantuan Bahan Ajar di SMA Maarif Lawang - Alfian Nur Muzaki; Tuti Mutia (Jayapangus Press, 2023)
Learning outcomes influenced several components, namely learning methods, learning environment, and social interaction. Problems encountered when observations were students less active during the lesson, less enthusiastic when following lesson, and didn’t pay attention teacher when explaining. This is caused teacher's learning methods being monotonous and lacking in variety. Only few students are active in their learning so can have an impact on cognitive learning outcomes. Learning model can increase student activity and learning outcomes through NHT learning model. Research aim is determine whether NHT learning model can improve learning outcomes of class X MIPA students on atmospheric material assisted by teaching materials. Research type is classroom action research with participant types. Classroom action research stages carried out included planning, implementation, observation, and reflection carried out through two cycles. Data collection techniques use tests, observation, and documentation. Instrument research used observation sheets and test question sheets. Data analysis technique uses descriptive. Research results showed that individual learning outcomes in pre-cycle were 66.45 with a fairly good classification. Average value for cycle 1 was 71.50 with a fairly good classification. Average value of cycle 2 was 79.79 with good classification. NHT learning model has a positive impact in improving individual students' cognitive learning outcomes. Then, learning outcomes with group activities using the NHT learning model also increased by 3.33 points with percentage increase of 3.70%-16.66% in cycle 2. Thus, NHT learning model was successful in improving cognitive learning outcomes of class X students MIPA at Maarif Lawang High School.